PENGARUH FINANCIAL ATTITUDE TERHADAP PERILAKU INDIVIDU DALAM MANAJEMEN KEUANGAN DI KALANGAN REMAJA - Maulida Khaerunnisa, Dila; Hatimatunnisani, Hani; Tazzudin, Muhamad Dimas; Lestari, Ceri; Haryono, Rakhmat (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Politeknik Pajajaran ICB Bandung, 2024)
A good financial attitude is the key to achieving financial stability in this era of uncertainty. One is to avoid some risks in facing unexpected situations. This study aims to find out whether financial attitude affects individual behavior in financial management. The method used in this analysis is a quantitative research method. The data collection technique used was a questionnaire. The respondents in this study were 111 early adolescence to late adolescence who were spread through several social media. The results of the study were obtained that there was a significant influence between financial attitude on personal behavior in financial management among ADOLESCENTS. The coefficient of determination value of 21.1% shows that the influence is quite large. This shows that the better the level of understanding among adolescence in determining their financial attitudes, the better their behavior in managing their finances.